To work or to study? Postmigration educational investments of adult refugees in Germany – Evidence from a choice experiment. (June 2021) - Damelang, Andreas; Kosyakova, Yuliya
Highlights: We study the determinants of and barriers to refugees' investments in education using a choice experiment introduced in a longitudinal survey of refugees in Germany. Our results follow the predictions from the immigrant human capital investment model combined with a basic model of educational decisions. Refugees' incentives to invest in education are shaped by skill transferability, settlement intentions, cost–benefit calculation and probability of success. Despite the different migration motives and experiences, the factors relevant to immigrant integration seem to apply to refugees as well. Abstract: In this article, we analyze individual factors and situational conditions under which immigrants are more or less likely to invest in host country-specific human capital. Theoretically, we root our expectations in a strand of the immigrant human capital investment model combined with a basic model of educational decisions. Using a choice experiment, we simulate a decision process among refugees in Germany and examine the determinants of investment preferences into host country-specific credentials, such as vocational education, as an alternative to an immediately available job offer. The choice experiment was introduced in the IAB-BAMF-SOEP Survey of Refugees, a representative longitudinal survey of recently arrived refugees in Germany. We find that refugees' intentions of investing in vocational education are guided by the transferability of foreign human capital, the time horizon to reap investments, and rational cost–benefit calculations. The probability of success is influential on its own but also bolsters the relevance of costs and benefits in educational choices.